BIBLIOMETRIC ANALYSIS USING VOSVIEWERS WITH PUBLISH OR PERISH OF “ART-BASED RESEARCH” - Youpika, Fitra (Program Studi Pendidikan Seni Musik UPI, 2024)
The purpose of this research is to analyze the trend of art-based research (ABR) using the bibliometric analysis method assisted by mapping analysis. The bibliometric analysis method and mapping analysis with VOSviewer were used in this research. Data sources were taken from the Google Scholar database in the period 2014–2023. The total number of documents found during the last 11 years was 921. The results showed that the development of ABR has generally experienced unstable changes over the past 11 years. The development of ABR is still experiencing ups and downs. From 2013 to 2014, ABR research experienced a decrease from 43 to 33 documents; from 2014–2015 experienced an increase from 33 to 50; from 2015–2016 experienced a slight increase from 50 to 51; and from 2016–2017 experienced an increase from 51 to 70. 2017-2018 remained from 70 to 70, then 2018-2019 experienced an increase from 70 to 82, 2019-2020 experienced an increase from 82 to 101, 2020-2021 again experienced a significant increase from 101 to 128, 2021-2022 again increased from 128 to 151, and in 2022 there was a decrease from 151 to 142. Based on this analysis, it can be concluded that the trend of ABR research from year to year has not been stable. In other words, ABR research still experiences ups and downs. However, overall, there has been an increase. Thus, research on ABR still needs to be done.